2019
DOI: 10.1186/s13018-019-1270-2
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative allogenic blood transfusion increases the incidence of postoperative deep vein thrombosis in total knee and hip arthroplasty

Abstract: Background Excessive blood loss caused by total joint arthroplasty (TJA) often increases the requirement for blood transfusion, which is associated with adverse outcomes. The purpose of this study was to determine the relationship between perioperative transfusion and postoperative DVT in TJA. Methods This retrospective study reviewed medical records of 715 patients, who consecutively underwent primary unilateral total knee arthroplasty (TKA) or total hip arthroplasty (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 40 publications
1
23
1
Order By: Relevance
“…Rodgers et al reported that epidural anesthesia reduced DVT incidence compared to general anesthesia [ 31 ]. Jiang et al also reported that perioperative allogenic blood transfusion was significantly related to DVT following total joint arthroplasty [ 32 ]. However, there is a paucity of literature regarding DVT after TKA with the use of anticoagulation chemoprophylaxis in the Asian population.…”
Section: Discussionmentioning
confidence: 99%
“…Rodgers et al reported that epidural anesthesia reduced DVT incidence compared to general anesthesia [ 31 ]. Jiang et al also reported that perioperative allogenic blood transfusion was significantly related to DVT following total joint arthroplasty [ 32 ]. However, there is a paucity of literature regarding DVT after TKA with the use of anticoagulation chemoprophylaxis in the Asian population.…”
Section: Discussionmentioning
confidence: 99%
“…Jackson, Hart, Frisch et al reported that perioperative RBC infusion does not significantly increase the incidence of venous thromboembolism (VTE) after total joint replacement [ 14 16 ]. Rothstein, Helm, Jiang, Goel, Dillon et al proved that perioperative RBC infusion would increase the risk of VTE in patients undergoing surgery [ 8 13 ], such as pediatric surgery [ 8 ], ventral hernia repair [ 9 ], total knee and hip arthroplasty [ 10 ]. It is necessary to conduct PSM analysis of perioperative RBC infusion and DVT.…”
Section: Discussionmentioning
confidence: 99%
“…Bone trauma patients are at high risk of DVT.A large number of literatures have reported the risk factors related to DVT in patients with perioperative bone trauma, such as lower extremity and pelvic fracture, high energy trauma, Glasgow score, prolonged preoperative waiting time, long operative time, advanced age, obesity, and history of malignant tumor [11][12][13] . The relationship between perioperative RBC infusion and the risk of DVT is controversial.Jackson, Hart, Frisch et al reported that perioperative erythrocyte infusion does not signi cantly increase the incidence of venous thromboembolism (VTE) after total joint replacement [14][15][16] .Rothstein,Helm,Jiang, Goel, Dillon et al proved that perioperative RBC infusion would increase the risk of VTE [3,6,8,[17][18][19] . In recent years, studies on the correlation between the two have drawn contradictory conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the correlation between perioperative RBC infusion and DVT has not yet been concluded, and even contradictory conclusions have appeared. It is reported that the RBC infusion rate of patients undergoing total knee arthroplasty is 10-20% [8,9] . Patients with severe bone trauma suffer from traumatic blood loss before surgery, and face the risk of bleeding during and after surgery, and the perioperative RBC infusion rate is not low.…”
Section: Introductionmentioning
confidence: 99%